Perbandingan Efektivitas Penggunaan Donepezil dan Memantine Terhadap Perbaikan Fungsi Kognitif pada Penyakit Alzheimer - Alamri, Khairun N. H.; Posangi, Jimmy; Nangoy, Edward (Jurnal Biomedik : JBM, 2021)
Abstract: Pharmacological therapy for Alzheimer’s disease are cholinesterase inhibitors (donepezil) and N-methyl-D-aspartate (memantine) receptor antagonists. The use of donepezil and memantine in elderly patients must be considered because they can affect the pharmacokinetic process of drugs and the effect of drugs on the body.The aim of the study was knowing the difference in the effectiveness of using Donepezil and Memantine on the improvement of cognitive function in Alzheimer's patients. This study was in the form of a literature review with data searches using three databases, namely Pubmed, ClinicalKey, Science Direct.  Keywords used are Donepezil AND Cognitive .AND Alzheimer, Memantine AND Cognitive AND Alzheimer. After being selected, 12 literature was obtained based on inclusion and exclusion criteria. In this study, Donepezil and memantine are beneficial in improving cognitive function in moderate to severe Alzheimer's disease but side effects tend to be more frequent with the use of donepezil than memantine. donepezil and memantine can be combined for the treatment of Alzheimer's disease but must pay attention to the effectiveness in clinical evaluation of patients and the cost effectiveness of the combination. Conclusion: Memantine and donepezil are effective and safe to use as therapy for moderate to severe Alzheimer’s disease. Donepezil and memantine combination therapy is more effective than donepezil or memantine monotherapy.Keywords: Donepezil, Memantine, Cognitive, Alzheimer  Abstrak: Terapi farmakologi untuk penyakit alzheimer adalah inhibitor kolinesterase (donepezil) dan antagonis reseptor N-metil-D-aspartat (memantine). Penggunaan donepezil dan memantine pada pasien lanjut usia harus diperhatikan karena dapat mempengaruhi proses farmakokinetik obat dan efek obat terhadap tubuh. Penelitian ini bertujuan untuk mengetahui perbedaan efektivitas penggunaan Donepezil dan Memantine terhadap peningkatan fungsi kognitif pada pasien Alzheimer. Penelitian ini berbentuk Literature Review dengan pencarian data menggunakan tiga database yaitu Pubmed, ClinicalKey, Science Direct. Kata kunci yang digunakan adalah Donepezil AND Cognitive AND Alzheimer, Memantine AND Cognitive AND Alzheimer. Setelah dipilih, diperoleh 12 literatur berdasarkan kriteria inklusi dan eksklusi. Dalam penelitian ini, Donepezil dan memantine bermanfaat dalam meningkatkan fungsi kognitif pada penyakit Alzheimer sedang hingga berat tetapi efek sampingnya cenderung lebih sering dengan penggunaan donepezil daripada memantine. donepezil dan memantine dapat digabungkan untuk pengobatan penyakit Alzheimer tetapi harus memperhatikan keefektifan dalam evaluasi klinis pasien dan efektivitas biaya dari kombinasi tersebut. Kesimpulan: Memantine dan donepezil efektif dan aman digunakan sebagai terapi penyakit Alzheimer sedang hingga berat. Terapi kombinasi donepezil dan memantine lebih efektif dibandingkan dengan monoterapi donepezil atau memantine.Kata Kunci : Donepezil, Memantine, Cognitive, Alzheimer